Identifikasi asam laurat pada susu formula bayi 0-6 bulan menggunakan kromatografi gas - Dwi Ernawati; Titin Aryani (Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Background: Given the importance of the presence of lauric acid and an alternative to breast milk in infants ages 0 months are the formula it will be measured levels of lauric acid in infant formula. Objective: The object of this study is the formula of infants aged 0-6 months circulating in Yogyakarta. The study was conducted at the Laboratory of Organic Chemistry University of Gadjah Mada in March-June, 2016. Methods: This study is a quantitative research experiments using Gas Chromatography-Mass Spectroscophy. Lauric fatty acids in infant formula can be obtained by identifying the peaks that appeared on the chromatogram by predicting the group of compounds which appear in the mass spectrometer. While quantitative data levels of omega-3 may be obtained by reading the percent relative peak area as a percent of the component compounds being analyzed. Result: Mean of the lauric acid content in infant formula for infants ages 0-6 months as much as 10.187%. Conclusion: There is a lauric acid content in the formula for infants ages 0-6 months